Analisis Pesan Moral dalam Puisi “Senja di Pelabuhan Kecil” Karya Chairil Anwar - Ina Sumiati; Sefina Aprilia Soleha (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
A literary work is a written or oral work that is conveyed using language as the main medium, which is a person's expression created based on thoughts, experiences, opinions and feelings. Poetry is a form of literary art that combines the beauty of language, emotion and imagination to express feelings and ideas in depth. Poetry contains the author's emotions and experiences that remain imprinted in memory. Poetry has hidden meanings wrapped in rhyming language so it is more interesting to read. The author is interested in analyzing the poem